Association of Interleukin-6 Gene Expression and Polymorphism With Incidence of Non-Hodgkin Lymphoma Disease Within the Iraqi Population - Ali, Hiyam Deea; Altaee, Maha Fakhry (Iraqi Journal of Science, 2026)
Lymphomas are broad tumors originating in the lymphatic system, causing lymph node enlargement. Non-Hodgkin lymphoma (NHL) is a group of blood cancers that includes all types of lymphomas except Hodgkin lymphomas. The Interleukin-6 (IL-6) gene is associated with various malignancies and can influence tumor growth and immune responses. This paper aims to study the role of IL-6 gene expression and polymorphisms in association with increased incidence of non-Hodgkin lymphoma. The study included 100 participants (50 NHL patients and 50 controls). Sex, age (divide into three groups), family history, CBC, and some kidney function tests were studied for both groups. This study emphasizes the role of IL-6 gene expression and polymorphisms, particularly the SNPs rs1800795 G/C, rs1800796 G/C, and rs1800797 G/A, with NHL incidence in the Iraqi population. The results showed a significant variation for all studied demographic and clinical data except with sex, family history, creatinine, smoking, and alcohol between NHL patients and healthy controls. Moreover, the median of the fold change of IL-6 gene expression (2-ΔΔCt) revealed down-regulation in NHL patients (0.04) with respect to control, which was (1). According to studied SNPs, some genotypes and alleles appeared to have significant protective effects while others appeared to be a risk factor that plays a significant role in increasing NHL incidence (large number of deaths for patients). In conclusion, the results of our investigation of an Iraqi Arab population revealed significant associations between the IL-6 gene and NHL.